Enhancing organizational citizenship behaviors through HRM practices: insights from employee perceptions in Moroccan firms - Hasinat, Imane; Hjouji, Zaynab; Loulidi, Sofia (Business, Management and Economics Engineering, 2026)
Research purpose – This study examines the impact of Human Resource Management (HRM) practices: recruitment, training, compensation, and performance evaluation, on employees’ Organisational Citizenship Behaviour (OCB) in Moroccan companies.Research methodology – A quantitative approach was employed. Data were collected via a structured questionnaire from 209 non-HR employees across various Moroccan companies. Exploratory Factor Analysis (EFA) was conducted to examine the measurement structure, followed by Structural Equation Modelling (SEM) to assess the relationships between HRM practices and OCB.Findings – HRM practices have a positive and significant influence on OCB. Training and compensation showed notable effects, while recruitment and performance evaluation also contributed to fostering a positive work environment, enhancing employee engagement, and encouraging behaviours beyond formal job requirements. These results highlight the pivotal role of HRM in promoting organisational commitment and discretionary behaviours.Research limitations – The use of a convenience sample and self-reported data limits generalisability and may introduce bias. The quantitative design does not fully capture the complexity of employee experiences, and data collection faced constraints due to refusals and limited collaboration. The study does not investigate the relationship between HRM practices and counterproductive behaviours, suggesting avenues for future research.Practical implications – Managers should prioritise transparent recruitment, continuous training, fair compensation, and objective performance evaluations to encourage OCB. These practices help cultivate a motivated and collaborative workforce, supporting organisational productivity and a positive work environment.Originality/Value – This study contributes uniquely by examining the effect of HRM practices on OCB in the Moroccan context, which remains underexplored. By focusing on employee perceptions, it provides actionable insights for HRM research and policy, helping organisations enhance work behaviour and overall performance.